A Markov-switching approach to the study of citations in academic journals. Issue 4 (November 2020) - Delbianco, Fernando; Fioriti, Andrés; Hernandez-Chanto, Allan; Tohmé, Fernando
Highlights: This paper introduces a Markovian approach to study the stability and growth of citations in academic journals. We propose a series of indexes to explain the series of citations available in the Web of Science for the period 1997–2018. We conduct an econometric analysis to characterize the regime-switching structure of the series studied. The series of citations exhibit a stable growth, remaining majorly in a dominant regime. Abstract: In this paper, we introduce a Markovian approach to study the stability and growth of citations in academic journals by featuring a regime-switching analysis. We characterize the regime structure exhibited by the series of citations available in the Web of Science database and determine the series' transition probabilities across regimes. Our main result shows that for most of the journals studied, the series of citations exhibit a stable growth, remaining majorly in a dominant regime identified as one of low or high number of citations.